EDI Failure: Experiences of Racialized Interpersonal Misconduct and the Delegation of Moral Responsibility - Tomlinson, Olivia (Journal of business ethics, 2025)
This paper investigates how responsibility for addressing interpersonal misconduct within organizations is managed as part of equity, diversity, and inclusion (EDI) efforts. Despite progress in promoting workplace EDI, the management of interpersonal misconduct tends to be individualized rather than systemically addressed. Drawing on qualitative data from a national survey of UK workers, we investigate employees' experiences of racialized misconduct and their perceptions of organizational responses to these events. Our research surfaces a prevalent empirical phenomenon whereby individuals perceive they are tasked with managing and resolving issues of abuse, bullying, and incivility. We understand this through the concept of responsibilization, as a delegation of moral responsibility where organizational structures and policies, shaped by reflexive subjectivity, shift responsibility onto individuals. When individuals cannot or will not take on this responsibility, entrenched patterns of inaction and superficial problem-solving lead to suboptimal outcomes for targets and bystanders. By reframing interpersonal misconduct as an object of responsibilization, our findings prompt a re-evaluation of organizational approaches to EDI management. This research illuminates the need for systemic changes that move beyond individual culpability and instead emphasize the value of ethical and relational management in responding to interpersonal misconduct.